Critical Discourse Analysis of the Existence of Gauk Lao Tengngae Cultural Values in Resolving Family Conflicts and Strengthening Religious Moderation in Palopo City - Rafikatul Aulia Sultan; Abdain; Firman Muhammad Arif (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Gauk Lao Tengngae is a local cultural tradition of the Luwu community that plays a strategic role in resolving family conflicts and is an important instrument in strengthening religious moderation in Palopo City. In the context of a multicultural society, the values contained in this tradition require in-depth analysis to understand their relevance to contemporary social dynamics. This study aims to critically analyze the discourse that has developed around the existence of Gauk Lao Tengngae cultural values in resolving family conflicts, as well as to explore its contribution to strengthening religious moderation in Palopo City through a critical discourse analysis approach. The study uses a qualitative approach with the Norman Fairclough model of critical discourse analysis (CDA). Data were obtained through in-depth interviews with traditional figures, religious leaders, and families who have experienced conflict and practice the Gauk Lao Tengngae tradition. The analysis was conducted in three dimensions: text, discursive practices, and socio-cultural practices. The analysis shows that Gauk Lao Tengngae cultural values contain principles of moderation that are in line with the teachings of religious tolerance, including: (1) the principle of deliberation and consensus in resolving conflicts; (2) respect for inclusive ancestral wisdom; (3) a mediation mechanism that prioritizes social harmony; and (4) the integration of universal human values across religions. The dominant discourse that has developed indicates that this tradition functions as a "cultural bridge" that strengthens social cohesion in a multi-religious society. Gauk Lao Tengngae has been proven to have a strong existence as social capital in strengthening religious moderation in Palopo City. The values contained therein can be a model for conflict resolution based on local wisdom, while strengthening tolerance and harmony between religious communities. This study recommends the need for revitalization and institutionalization of the Gauk Lao Tengngae tradition as part of a strategy for developing a moderate and tolerant national character.